The Correlation Between Sustainable Leadership Practices and Teacher Leadership in junior High Schools in Woha District, Bima, West Nusa Tenggara - Mila Septian Haryati; Noryana binti Ahmad Khusaini; Ibnu Khaldun Sudirman; Mahaliza Mansor (Jurnal Pendidikan, Sains, Geologi, dan Geofisika (GeoScienceEd Journal), 2026)
Sustainable leadership of the principal as a leadership style that focuses on improving andimplementing professional tasks in the school including for a teacher to lead is related to oneanother. To create a teacher leadership process and implementation, it is always related to how aleader behaves and makes improvements every time for long-term goals. Sustainable leadershippractices are considered to often contribute to teacher leadership practices in schools (Cook,2014). In parallel, a descriptive research survey was conducted to identify sustainable leadershippractices of principals and correlations of levels of teacher leadership practices. This researchinvolved junior high school woha bima NTB Indonesia. The population of respondents in thisstudy were all senior teachers, amounting to 85 people. Data were analyzed using scores,standard deviations and person correlations. Data were collected using a questionnaire developedand modified by the theory of sustainable leadership established by Hargreaves and Fink (2006)and the theory of teacher leadership by Ktzenmeyer & Moller (2001). The results of the studyfound that the sustainable leadership of the principal has a strong positive relationship at thesignificant level of p> 0,000 between the sustainable leadership of the principal and theleadership of the teacher at SMP Woha Bima, NTB. The Pearson value of r = 0.719 indicates thatsustainable leadership practices have a strong enough relationship with the level of teacherleadership practices in SMP Negeri Woha District, Bima Regency, NTB. Thus, the results of theperson correlation test study showed a significant relationship between sustainable teacherleadership practices and teacher leadership.